Factors Associated with Successful Vaginal Birth after a Caesarean Section: a Cross-sectional Study at Institute of Woman and Child Health, Bangladesh - Ara, Anjuman; Khan, Sanjida; Akhter, Sanjida; Shamsun Nahar, Begum; Akter, Easmin; Begum, Ferdousi (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Background: The rate of caesarean section (CS) deliveries has been increasing considerably worldwide and is a rising concern in many countries like Bangladesh. Now-a-days, the majority of CS in an institution is usually done for history of previous CS. Planning a vaginal birth after caesarean (VBAC) is considered a reasonable choice for women in a subsequent pregnancy. However, this may increase the risk of adverse outcomes such as uterine rupture. The factors affecting VBAC should be evaluated to reduce the risk. This study aimed to determine the factors associated with successful VBAC. Materials & Methods: A cross-sectional study was conducted on 137 women selected for VBAC at the Institute of Woman and Child Health, Dhaka, Bangladesh, from August 2020 to September 2022. Information regarding previous and current pregnancies were recorded. A descriptive and inferential analysis was performed using SPSS version 25.0. Results: The mean age of the participants was 25.4±3.2 years and majority of participants were in the age group 20-29 years (67.9%) and housewives (89.1%). About 8.8% of women had more than one previous CS. The VBAC success rate was 69.3%. Factors associated with successful VBAC were average body mass index (BMI) (p=0.002), gestational age 37-40 weeks at delivery (p=0.037), the ruptured membrane at admission (p Conclusions: In properly selected cases, a reasonable success rate of VBAC can be achieved. Factors that are associated with successful VBAC include having an average BMI, gestational age of 37-40 weeks, spontaneous onset of labor, the ruptured membrane at admission (p<0.001), spontaneous labour (p<0.001), sweeping or stretching as the type of induction (p<0.001), and in ultrasonography estimated fetal weight (EFW) 2.5-3.0 kg (p=0.002). Bangladesh J Obstet Gynaecol, 2023; Vol. 38(2): 64-70